PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN NET PROFIT MARGIN TERHADAP RETURN SAHAM PADA PERUSAHAAN KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2017 - Fatansiru, Nalindri Arin; Merdiana, Candra Vionela (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to analyze the effect of Current Ratio, Debt toEquity Ratio, and Net Profit Margin on stock returns of case studies in companies cosmetics and household goods listed on the Indonesia Stock Exchange period 2012-2017 Independent variables used in this study are Current Ratio, Debt to Equity Ratio, and Net Profit Margin while the dependent variable is stock returns. The population in this study is all cosmetics and household goods companies for the period 2012-2017. Based on the purposive sampling method obtained 5 samples. Data type used is secondary data. Data obtained by the method of documentation. The analysis technique used is the Panel Data Regression Analysis. The results of multiple linear regression analysis with a significant level of 5%, then it can concluded that the first hypothesis Current Ratio of 0.02 has a negative effect and significant towards stock returns, the second hypothesis is Debt to Equity Ratio of 0.90 positive and not significant effect on stock returns, the third hypothesis is Net Profit Margin of 0.08 has no effect on stock returns, hypotheses fourth, Current Ratio, Debt to Equity Ratio, and Net Profit Margin of 0.015726 simultaneously affect stock returns.